2016
DOI: 10.1108/jocm-01-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel study of transformational leadership, dual organizational change and innovative behavior in groups

Abstract: Purpose Based on dual organizational theory, the purpose of this paper is to examine the relationship between transformational leadership and innovative behavior in groups. The authors proposed that group innovative behavior was influenced by transformational leadership as a group-level construct which was moderated by dual organizational change that represent organization-level resources. Furthermore, the authors identified two organizational change-related situational variables-radical change and incremental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 77 publications
2
37
0
4
Order By: Relevance
“…Transformational leadership styles can provide useful feedback to employees, encourage them to make additional efforts to achieve new solutions, and increase their intrinsic motivation for creative thinking (Choi et al, 2016). Transformational leadership style can motivate employees to achieve goals with higher self-reinforcement, rather than developing reciprocal exchange relationships with them (Feng et al, 2016). Craig et al (2015) evaluated the effects of different leadership styles in longitudinal laboratory experiments, and the results showed that transformational leadership had a more positive effect on group effectiveness than transactional leadership.…”
Section: Transformational Leadership and Employee Performancementioning
confidence: 99%
“…Transformational leadership styles can provide useful feedback to employees, encourage them to make additional efforts to achieve new solutions, and increase their intrinsic motivation for creative thinking (Choi et al, 2016). Transformational leadership style can motivate employees to achieve goals with higher self-reinforcement, rather than developing reciprocal exchange relationships with them (Feng et al, 2016). Craig et al (2015) evaluated the effects of different leadership styles in longitudinal laboratory experiments, and the results showed that transformational leadership had a more positive effect on group effectiveness than transactional leadership.…”
Section: Transformational Leadership and Employee Performancementioning
confidence: 99%
“…Furthermore, he identified two organizational change-related situational variables-radical change and incremental change and examined their effects on group innovative behavior. Researchers concluded in research that group innovative behavior was positively related to transformational leadership and the relationship between them was moderated by radical change, the incremental change was not there, the other relationship was also found among the both changes that radical and incremental changes have positive relationship with group innovative behavior (Feng, Huang & Zhang, 2016). It is proved and the researchers believed in many studies that in manufacturing companies transformational leadership style is very effective because it guides the employees towards new product development, more profitability, and improved performance by using the exploratory leadership.…”
Section: Transformational Leadership Relationship With Organizationalmentioning
confidence: 99%
“…' Previous researchers believed that in spite of agreement on the importance of leadership for innovation, little research has been done on the nature of this link (Mumford, 2002;García-Morales, Matías-Reche, & Hurtado-Torres, 2008;Jung, Chow, & Wu, 2008;Gumusluoglu & Ilsev, 2009a;Hsiao, Chang, & Tu, 2009;Oke, Munshi, & Walumbwa, 2009;Makri & Scandura, 2010). It has been argued that previous studies in the field of innovation and leadership are not sufficiently benefited by each other and mostly studied in separate areas (Imran & Anis-ul-Haque, 2011;Feng, Huang, & Zhang, 2016;Prasad & Junni, 2016).…”
Section: Introductionmentioning
confidence: 99%